Judges' Considerations On Traffic Accident Cases In Relation To The Law On Road Traffic And Transportation (Decision Study Number: 35/Pid.Sus/2022/Pn.Pwk) - Sampurna Banyuaji, Sampurna; Guntara, Deny; Abas, Muhamad (Dinasti Research, 2025)
This study analyzes law enforcement in traffic accident cases resulting in fatalities, focusing on Article 310 paragraph (4) of Law Number 22 of 2009 concerning Road Traffic and Transportation. The main objective is to examine how the law is applied and how judges make considerations in handing down verdicts. Using a normative legal research method, this study analyzes Judgment No. 35/Pid.Sus/2022/PN.Pwk. The results show that the defendant, who was negligent and caused the victim's death, was indeed charged under this article, which carries a maximum sentence of six years in prison. However, an interesting finding from this study is the gap between the maximum penalty and the sentence imposed. Although the defendant's actions were proven to violate the article and cause death, the judge imposed a sentence of 4 years in prison, which is lighter than the maximum penalty. This decision was based on legal and non-legal considerations, including mitigating and aggravating factors. It is concluded that this lighter sentence than the maximum penalty is considered contrary to the spirit of Article 310(4) of the LLAJ Law.